2010
DOI: 10.1021/jf101004z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Health-Related Compounds in Eggplant (Solanum melongena L.) Lines Derived from Introgression of Allied Species

Abstract: The purpose of the present study was to investigate the levels of either the nutraceutical and health-promoting compounds or the antioxidant properties of innovative eggplant (Solanum melongena L.) genotypes tolerant and/or resistant to fungi, derived from conventional and non-conventional breeding methodologies (i.e., sexual interspecific hybridization, interspecific protoplast electrofusion, androgenesis, and backcross cycles) in comparison with their allied and cultivated parents. Chemical measures of solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
62
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 54 publications
10
62
1
6
Order By: Relevance
“…We did not find a relation between the amount of chlorogenic acid and browning pulp. These results seems to be confirmed by those obtained by Bhowmik and Dris (2004) and by Mennella et al (2010), who reported a high potential browning variability with respect to other traits, due to the influence of different factors, such as polyphenol quality and quantity, intrinsic enzyme activity and acidity of the medium.…”
Section: Discussionsupporting
confidence: 86%
“…We did not find a relation between the amount of chlorogenic acid and browning pulp. These results seems to be confirmed by those obtained by Bhowmik and Dris (2004) and by Mennella et al (2010), who reported a high potential browning variability with respect to other traits, due to the influence of different factors, such as polyphenol quality and quantity, intrinsic enzyme activity and acidity of the medium.…”
Section: Discussionsupporting
confidence: 86%
“…However, sexual hybrids often have a high degree of sterility (Daunay et al 1993;Isshiki and Taura 2003). Development of progenies with increased fertility from hybrids has been obtained by sexual crosses using the interspecific hybrids as female parents (Khan and Isshiki 2010) or by means of somatic hybridization followed by anther culture of the hybrids or of progenies obtained after crossing the tetraploid somatic hybrids with tetraploid S. melongena (Daunay et al 1993;Rizza et al 2002;Toppino et al 2008;Mennella et al 2010). In our case, by using the recurrent parents as males first backcross seeds, which we have used here for the characterization of the plants and fruits, could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Although a first backcross generation to S. melongena has been reported (Schaff et al 1982), no records document introgression of S. macrocarpon genes into S. melongena. Interspecific sexual and somatic hybrids between S. melongena and S. aethiopicum are easier to produce and although they present a high degree of sterility, backcross generations to S. melongena with introgressions of S. aethiopicum have been obtained on occasion (Rizza et al 2002;Toppino et al 2008;Khan and Isshiki 2010;Mennella et al 2010). Therefore, generations derived from crosses between S. aethiopicum and S. melongena seem the most promising for the breeding of both crops.…”
Section: Introductionmentioning
confidence: 99%
“…Eggplant fruit is a rich source of vitamins and dietary fibers, as well as phytonutrients, mainly phenolic compounds such as caffeic and chlorogenic acids, and flavonoids (Hanson et al 2006;Singh et al 2009;Mennella et al 2010;Das et al 2011). The established health-promoting properties have led to an increase in the consumption of eggplant fruits in recent years (Akanitapichat et al 2010).…”
Section: Introductionmentioning
confidence: 99%